Assessment of different drying methods and application of some chemical compounds in prevention of corn contamination by Fumonisin - Mortazavi, Shohreh; Mohtadinia, Javad; Kazemi, Abdolhassan (Progress in Nutrition, 2019)
The present study aimed to assess prevention of fungal growth and fumonisin production in corn by chemical methods at different levels. The anti-fungal properties of a series of chemical compounds at different levels were tested on yeast chloramphenicol glucose agar. The positive samples to fusarium were separated to measure fumonoisin content by ELISA. Among the chemical compounds, sorbic acid at 0.5-1.5% concentrations, sodium metabisulphite at 0.5-1.5% concentrations, benzoic acid at 0.5-1.5% concentrations, and propionic acid at 1.5% concentration completely inhibited Fusarium verticillioides growth and fumonisin production. Not only did sulfur dioxide gas (SO2) and sodium metabisulphite at 1.5% concentration completely inhibited Fusarium growth, but they also prevented the growth of all fungi and no mold was observed on the plates. Thus, propionic acid had tolerable (50-75%) anti-fungal properties, but was ineffective in complete prevention of Fusarium.